(untitled) (Revista Brasileira de Contabilidade e Gestão, 2025)
The objective of this study was to assess the mediating impacts of behavioral preferences on the contributions of companies’ contingency factors on ABC implementation. The study was conducted in Tanzania where the primary data were collected from 107 sample of service companies based on cross-sectional survey design. Analysis was done on the partial least squares - structural equation modeling (PLS-SEM) using SmartPLS4 software and SPSS 28.0.1. Results showed that, of the three elements of behavioral preferences it was only perceived usefulness and perceived ease of use that positively mediated the causal relationships between the competitiveness, business culture and ABC implementation.